ANALISIS USER ACCEPTANCE TEST PADA APLIKASI PENGIRIMAN BARANG DALAM MENENTUKAN KUALITAS SISTEM - Kusuma, Abdi Pandu; Yufron, Ahmad (Antivirus : Jurnal Ilmiah Teknik Informatika, 2024)
An application is a type of software or program that runs on a system. It can be either a computer or mobile device[1]. Applications should be tested all the way to the end user in order to have a clear understanding of the actual user and their experience with a product through feedback from customers who have had first hand experience with the product[2]. Also, it is necessary to include user acceptance testing as it brings end users of the system to test functions within the system as to whether there is proper working of the features and if the user’s needs are catered for[3]. Therefore, the aim of this study is to evaluate the testing of the developed goods delivery system application among its end users with special focus on user acceptance testing. User acceptance testing is applied in this case using open beta testing. The searching aim is to test the interface of the goods delivery system application using user acceptance testing and later establish the accuracy of the testing of the system application. The data collection method was performed using interviews, observations, literature study and documentation which enabled effective data collection. The research was done through questionnaires which were sent to the end users with a sample size of 50 respondents. The dissemination of questionnaires is necessary as the first task of any testing activity using the User Acceptance Testing. The research on application testing processes using the User Acceptance Testing method and its aspects achieved a per cent accuracy level of 85% and testing decision resultant as “Agree” of 213.5.